Micro-Raman study of nanocomposite porous films with silver nanoparticles prepared using pulsed laser deposition - Strelchuk, V.V.; Kolomys, O.F.; Golichenko, B.O.; Boyko, M.I.; Kaganovich, E.B.; Krishchenko, I.M.; Kravchenko, S.O.; Lytvyn, O.S.; Manoilov, E.G.; Nasieka, Iu.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Nanocomposite porous films with silver nanoparticle (Ag NP) arrays were prepared by the pulsed laser deposition from the back flux of erosion torch particles in argon atmosphere on the substrate placed at the target plane. Preparation conditions of the films were set by argon pressure, energy density of laser pulses, their amount and substrate position relatively to the torch axis. The films were prepared with gradient thickness, variable Ag NP sizes and distance between them along the length of substrate as well as corresponding maxima in the spectra of local surface plasmon absorption. Plasmon effects of the Raman scattering enhance in the matter of the Ag NP shell gave the opportunity to register the spectral bands caused by an extremely small quantity of silver compounds with oxygen and carbon. The possible nature of individual bands in the Raman spectrum was analyzed. The obtained results are important for interpretation of the Raman spectra of analytes based on the prepared SERS substrates.